The clinical course of actinic keratosis correlates with underlying molecular mechanisms. (11th September 2019) - Bakshi, A.; Shafi, R.; Nelson, J.; Cantrell, W.C.; Subhadarshani, S.; Andea, A.; Athar, M.; Elmets, C.A.
Summary: Background: Actinic keratoses (AKs) are common premalignant skin lesions triggered by excessive ultraviolet exposure. The majority of AKs regress or persist, but some progress to squamous cell carcinomas. Biomarkers associated with their persistence, progression and regression have not been characterized. Objectives: We performed skin biopsies in patients with extensive actinic damage to identify biomarkers that correlate with clinical progression and regression of AKs. Methods: This was an observational study of a cohort of patients with extensive actinic damage. AKs were mapped on a clear plastic template in 26 patients at months 3, 6, 9 and 11. Biopsies were taken from randomly selected, predetermined AKs and were evaluated for p53, E‐cadherin, Snail, Slug and Twist. The study is registered at Clinicaltrials.gov: NCT00027976. Results: p53 exhibited greater expression in clinically apparent AKs (histological score 2·89 ± 1·45) than in regressed AKs (0·75 ± 0·96); P < 0·01. There was also significantly less membrane E‐cadherin, the lack of which is a marker of epithelial–mesenchymal transition, in clinically apparent AKs (1·89 ± 1·81) than in sun‐exposed skin (3·07 ± 1·75); P < 0·005. The E‐cadherin transcription repressors Snail, Slug and Twist were increased in AKs compared with sun‐exposed skin. A limitation of the study is that measurement of histological biomarkers was not a primary end point. In addition, patients were allowed to apply sunscreens. Conclusions: At the molecular level, loss of E‐cadherin and an increase in p53 are linked to the dynamic interplay between the persistence, progression and regression of AKs. What's already known about this topic? Actinic keratoses (AKs) are common dysplastic epidermal lesions that result from chronic and excessive ultraviolet exposure. Biomarkers associated with progression and regression of AK have not been characterized. What does this study add? Decreased E‐cadherin and increased p53, Snail, Slug and Twist (E‐cadherin transcription factors) were associated with progression from AK to nonmelanoma skin cancer. What is the translational message? Strategies targeting these molecules may be effective in reversing rising skin cancer rates. E‐cadherin, p53, Snail, Slug and Twist are potential biomarkers that may be used to assess the efficacy of existing chemopreventive agents. Abstract : Linked Comment: O'Shaughnessy. Br J Dermatol 2020; 182 :834–835.